Acute Acalculous Cholecystitis in Dengue Fever with Raised Transaminase - Kazi Shihab Uddin; Syed Minhaj Uddin Ahmed; Sabera Sultana; Habiba Akter; Marufa Rehnuma Azad; Rakibul Hasan (KYAMC Journal, 2024)
Background: Dengue fever is a viral fever classically characterized by high-grade temperature, headache, ocular pain, sternal pain, muscle and joint pain, nausea, vomiting and sometimes rash. Apart from above stated clinical features, there may be hepatitis, ascites, cholecystitis, pleural effusion, etc. which are confirmed by investigations. Objective: To establish the fact that acute acalculous cholecystitis is not uncommon in dengue fever. Raised transaminases are good indicators for further investigation and to find out the prognosis and management of acute acalculous cholecystitis in dengue fever. Materials and Methods: A total of 100 patients with confirmed dengue fever who were admitted to Khwaja Yunus Ali Medical College Hospital, were selected randomly for one month. Among them, 44 patients had undergone for ultrasound of the whole abdomen because of nausea, vomiting, abdominal pain and raised transaminases. Results: Acute acalculous cholecystitis was detected in 20 patients (20%) with confirmed dengue fever. These patients with acute acalculous cholecystitis were treated conservatively and they recovered completely without any surgical intervention. Conclusion: In dengue fever unlike acute pancreatitis or encephalitis, acute acalculous cholecystitis is not uncommon and it is self-limiting and resolved by conservative management. KYAMC Journal Volume: 14, No: 04, January 2024: 190-193.